Elephantine, Ägypten. Der Chnumtempel des Neuen Reiches - Arnold, Felix (e-Forschungsberichte des DAI, 2017)
The investigation of the relief decoration of the Khnum temple of the New Kingdom was continued in 2014 and 2015. The aim of this season was to complete the documentation of the blocks that had been reused in the temple house of Nectanebos II. The blocks appear to originate from at least two different buildings. The first building was a small barque station built by Queen Hatshepsut in the early part of her reign for the processional barque of Khnum. The second building was founded by Thutmosis I and finished or enlarged by Thutmosis II. Both buildings originally stood to the west of the main temple of Khnum, in the area later occupied by the temple house of Nectanebos II.